2007
DOI: 10.1093/molbev/msm180
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Clonality in the Little Fire Ant

Abstract: Reproduction systems are controlling the creation of new genetic variants as well as how natural selection can operate on these variants. Therefore, they had historically been one of the main foci of evolutionary biology studies. The little fire ant, Wasmannia auropunctata, has been found to display an extraordinary reproduction system, in which both males and female queens are produced clonally. So far, native sexual populations of W. auropunctata have not been identified. Our goals were to identify such sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 35 publications
6
95
1
Order By: Relevance
“…It is possible that sexual reproduction between queens and males (which usually generates workers) generates males if the queen's genome is successfully eliminated from the eggs [9]. Alternatively, it has been suggested that queens of at least one species (W. auropunctata) produce a small proportion of eggs that are non-nucleate (similar to the mechanism in Cupressus), and that these non-nucleate eggs give rise to androgenetic males if fertilized by sperm [51]. Given that queens of most ant species are highly fecund, the costs of producing non-nucleate eggs may be negligible if their number is low.…”
Section: (C) Androgenetic Antsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that sexual reproduction between queens and males (which usually generates workers) generates males if the queen's genome is successfully eliminated from the eggs [9]. Alternatively, it has been suggested that queens of at least one species (W. auropunctata) produce a small proportion of eggs that are non-nucleate (similar to the mechanism in Cupressus), and that these non-nucleate eggs give rise to androgenetic males if fertilized by sperm [51]. Given that queens of most ant species are highly fecund, the costs of producing non-nucleate eggs may be negligible if their number is low.…”
Section: (C) Androgenetic Antsmentioning
confidence: 99%
“…In the little fire ant, W. auropunctata, workers arise sexually, queens arise by thelytoky, and males arise androgenetically [9,11,51]. It is tempting to regard this situation as a classic evolutionary arms race in which males retaliate against the absence rstb.royalsocietypublishing.org Phil.…”
Section: Does Androgenesis Arise As a Consequence Of Inter-sexual Commentioning
confidence: 99%
“…In W. auropunctata, this unusual mating system is not induced by any of the most common endosymbiotic manipulators [15] and appears instead to be genetically determined [16]. Foucaud et al [10] demonstrated that W. auropunctata populations displaying a parthenogenesis-androgenesis system (hereafter referred to as 'clonal' populations, for simplicity) have recurrently emerged from ancestral classical haplo-diploid sexual populations (hereafter referred to as 'sexual' populations), in which females (i.e. queens and sterile workers) develop from diploid fertilized eggs and males develop from haploid unfertilized eggs (arrhenotoky).…”
Section: Introductionmentioning
confidence: 98%
“…Androgenesis has traditionally been regarded as a male trait, giving to androgenetic males a substantial fitness advantage over their sexually reproducing relatives [5]. Androgenesis has, to date, been identified as the main form of reproduction in a very small number of species from four distinct taxa: the hermaphrodite Saharan cypress tree Cupressus dupreziana [6], four hermaphrodite species of freshwater clams from the genus Corbicula [7], a hybrid complex of Bacillus stick insects [8,9], and three haplo-diploid ant species: Wasmannia auropunctata [10,11], Vollenhovia emeryi [12] and Paratrechina longicornis [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation